Molecular biomarkers of leukemia: convergence-based drug resistance mechanisms in chronic myeloid leukemia and myeloproliferative neoplasms - Kaehler, Meike; von Bubnoff, Nikolas; Cascorbi, Ingolf; Gorantla, Sivahari Prasad (Frontiers in Pharmacology, 2024)
Leukemia represents a diverse group of hematopoietic neoplasms that can be classified into different subtypes based on the molecular aberration in the affected cell population. Identification of these molecular classification is required to identify specific targeted therapeutic approaches for each leukemic subtype. In general, targeted therapy approaches achieve good responses in some leukemia subgroups, however, resistance against these targeted therapies is common. In this review, we summarize molecular drug resistance biomarkers in targeted therapies in BCR::ABL1-driven chronic myeloid leukemia (CML) and JAK2-driven myeloproliferative neoplasms (MPNs). While acquisition of secondary mutations in the BCR::ABL1 kinase domain is the a common mechanism associated with TKI resistance in CML, in JAK2-driven MPNs secondary mutations in JAK2 are rare. Due to high prevalence and lack of specific therapy approaches in MPNs compared to CML, identification of crucial pathways leading to inhibitor persistence in MPN model is utterly important. In this review, we focus on different alternative signaling pathways activated in both, BCR::ABL1-mediated CML and JAK2-mediated MPNs, by combining data from in vitro and in vivo-studies that could be used as potential biomarkers of drug resistance. In a nutshell, some common similarities, especially activation of PDGFR, Ras, PI3K/Akt signaling pathways, have been demonstrated in both leukemias. In addition, induction of the nucleoprotein YBX1 was shown to be involved in TKI-resistant JAK2-mediated MPN, as well as TKI-resistant CML highlighting deubiquitinating enzymes as potential biomarkers of TKI resistance. Taken together, whole exome sequencing of cell-based or patients-derived samples are highly beneficial to define specific resistance markers.Additionally, this might be helpful for the development of novel diagnostic tools, e.g. liquid biopsy, and novel therapeutic agents, which could be used to overcome TKI resistance in molecularly distinct leukemia subtypes.